V=x³-7x+6, V=(x-2)(x+3)*h
(x-2)(x+3)*h=x³-7x+6
h{x²+x-6}=x³-7x+6
h=(x³-7x+6)/(x²+x-6)
Therefore h=x-1
-----------------------------
Check answer:
V=(x-2)(x+3)(x-1)
=(x-1)(x²+x-6)
=x(x²+x-6)-1(x²+x-6)
=x³+x²-6x-x²-x+6
=x³-6x-x+6
=x³-7x+6
Answer:
Given:
Suppose Paul receives a 6% raise every year.
To find:
After four such raises, the total percentage increase to the nearest whole percent.
The formula used to calculate percentage is: (value/total value)*100%.
Step-by-step explanation:
Step 1 of 1
Assume his salary is originally 100 dollars.
Then, in the next year, he would have 106 dollars, and in the next, he would have 112.36 dollars.
The next year he would have 119.1016 dollars and in the final year, he would have 126.247.
As the total increase is,
((126.247 -100)/100) *100
= 26.247%
the answer is 26%.
Answer:
Step-by-step explanation:
Start by breaking up the question into parts:'always an odd number' . An even number is any number divisible 2 e.g. 2n, an odd number is always 1 higher or lower than an even number e.g. 2n+1 or something similar. Getting an answer at the end of working of this form will prove the theory'any two consecutive integers' means two numbers that are next to each other on the number line.To prove this, we can do this in terms of n i.e. n and n+1'the squares' square the two terms we have just written down to give n2 and (n+1)2The 'sum of the squares' tells us to add these two parts together. We would then hope to work through this and get something similar to the idea of 2n+1 or something similarn2+(n+1)2=2n2+2n+1=2(n2+n) +1. The first part of this is even because it is divisible by 2. By adding 1 it must become odd.